Protocol for in-vitro introduction and multiplication of Urochloa - CGIAR Research Program on Livestock (2020)
The procedure of disinfection and in-vitro sowing of materials corresponding to the Bh16 group of Urochloa humidicola was able to establish plants without high percentages of contamination by fungi/bacteria. Use of sulfuric acid for scarification before sowing was found to generate germination results similar to those obtained in silica sand.